Ana o 3‐specific IgE is a good predictor for clinically relevant cashew allergy in children. Issue 4 (17th November 2016) - Lange, L.; Lasota, L.; Finger, A.; Vlajnic, D.; Büsing, S.; Meister, J.; Broekaert, I.; Pfannenstiel, C.; Friedrichs, F.; Price, M.; Trendelenburg, V.; Niggemann, B.; et al.
Abstract: Introduction: Component‐resolved diagnostics using specific IgE to 2 S albumins has shown to be a valuable new option in diagnostic procedure. Ana o 3 is a 2 S albumin from cashew. The aim of this study was to investigate the role of Ana o 3‐specific serum IgE in the diagnosis of cashew allergy and to identify cut‐off levels to replace oral food challenges. Moreover, the value of additional determination of total IgE has been investigated. Methods: In a multicentre study, we analysed specific IgE to cashew extract and Ana o 3 as well as total IgE in children with suspected cashew allergy using the ImmunoCAP‐FEIA and a standardized diagnostic procedure including oral challenges where indicated. Results: A total of 61 patients were included in the study. Forty‐two were allergic to cashew, and 19 were tolerant. In receiver operating curves, Ana o 3 discriminates between allergic and tolerant children better than cashew‐specific IgE with an area under the curve of 0.94 vs 0.78. The ratio of Ana o 3‐specific IgE to total IgE did not further improve the diagnostic procedure. Probability curves for Ana o 3‐specific IgE have been calculated, and a 95% probability could be estimated at 2.0 kU/l. Conclusion: Specific IgE to Ana o 3 is a valuable tool for the diagnosis of cashew allergy. Considering its positive predictive value, it might allow to make a considerable number of oral challenges superfluous.